2012
DOI: 10.1039/c2nr11251e
|View full text |Cite
|
Sign up to set email alerts
|

Novel hollow mesoporous 1D TiO2 nanofibers as photovoltaic and photocatalytic materials

Abstract: Hollow mesoporous one dimensional (1D) TiO(2) nanofibers are successfully prepared by co-axial electrospinning of a titanium tetraisopropoxide (TTIP) solution with two immiscible polymers; polyethylene oxide (PEO) and polyvinylpyrrolidone (PVP) using a core-shell spinneret, followed by annealing at 450 °C. The annealed mesoporous TiO(2) nanofibers are found to having a hollow structure with an average diameter of 130 nm. Measurements using the Brunauer-Emmett-Teller (BET) method reveal that hollow mesoporous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 38 publications
1
138
0
Order By: Relevance
“…Polyethylene and polypropylene are two polymers that have been successfully fabricated from the melt [32,33]. Ceramic fibers such as TiO 2 have been fabricated from a sol of ceramic precursor and a host polymer such as polyvinylpyrrolidone (PVP) [34]. Metallic fibers such as copper fibers have also been generated by electrospinning a metal acetate or nitrate solution with a host polymer, followed by degradation of the host polymer and reduction [35].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene and polypropylene are two polymers that have been successfully fabricated from the melt [32,33]. Ceramic fibers such as TiO 2 have been fabricated from a sol of ceramic precursor and a host polymer such as polyvinylpyrrolidone (PVP) [34]. Metallic fibers such as copper fibers have also been generated by electrospinning a metal acetate or nitrate solution with a host polymer, followed by degradation of the host polymer and reduction [35].…”
Section: Introductionmentioning
confidence: 99%
“…Bijarbooneh et al (2013) have reported mesoporous anatase TiO2 nanofibers with a diameter of around 300 nm and 10-20 μm length show a conversion cell efficiency of 8.14%, corresponding to a ∼35% enhancement over the Degussa P25 reference photoanode. Zhang et al (2012b) reported hollow mesoporous TiO2 nanofibers prepared by co-axial electrospinning with two immiscible polymers, polyethylene oxide (PEO) and polyvinylpyrrolidone (PVP) (Figure 7a&b). The solar-to-current conversion efficiency (η) and short circuit current (Jsc) of these nanofibers were measured to be around 5.6% and 10.38 mA/cm 2 respectively, which were higher than those of DSSC made using regular TiO2 nanofibers under identical conditions (η=4.2%, Jsc = 8.99 mA/cm 2 ) ( Figure 7c).…”
Section: Tablementioning
confidence: 99%
“…The combination of metal-oxides in nanofibers can be obtained differently from the routes discussed earlier like doping or addition of metal oxides. One of the approaches is forming core/shell nanostructures of metal oxides where a metal oxide layer acts as a shell and another as core layer (Zhang et al, 2012b). Electrospinning technique is one of the very effective techniques in synthesizing core/shell nanostructures in different combinations of metal oxides.…”
Section: Photocatalysismentioning
confidence: 99%
“…TiO 2 nanostructures with controlled morphologies and exposed active sites have demonstrated considerable potential as photocatalysts for practical use in environmental protection and energy conversion systems [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%